The Interplay Between Colonial History and Postcolonial Institutions: Evidence from Cameroon - Mabeu, Marie Christelle; Pongou, Roland (Université d'Ottawa | University of Ottawa, 2021)
We study the long-term impacts of Cameroon's colonial history and its interplay with postcolonial institutions. We exploit both the arbitrary division of the German Colony of Kamerun between France and Britain after World War I and the 1961 reunification of British Southern Cameroons and the French-speaking République du Cameroun. Comparing individuals from the same ethnic homeland but living on either side of the British-French border within Cameroon, we find that individuals on the British side had higher educational attainment before the reunification, but that this initial advantage was partially erased by post-reunification governance. Despite achieving higher educational attainment overall, individuals on the British side have worse employment outcomes and roughly similar infant mortality rates. We provide further evidence of the interaction between colonial origins and postcolonial institutions by analyzing how the outcomes of individuals in former Southern Cameroons differ from their hypothetical outcomes, had they instead opted to join Nigeria in the 1961 plebiscite. We find that they have lower educational attainment, higher infant mortality rates, and worse employment outcomes relative to their co-ethnics living on the Nigerian side of the border between former Southern Cameroons and Nigeria.
Keywords: 2111E; Colonial history; Postcolonial institutions; Cameroon; British Southern Cameroons; French Cameroons; République du Cameroun; Reunification; Federalism; Centralization